The effect of polarity on the formation of streamers in an inhomogeneous electric field; Gas Discharge Plasmas and Their Applications (GDP 2019) - Beloplotov D. V.; Genin D. E.; Pechenitsin D. S.; Tarasenko V. F. Victor Fedotovich (2019, 2019)
Заглавие с титульного экрана